How The World Looks From Japan; Capital Rich Yet Resources Poor - Robert A. Brusca (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1990)
OUTLINE Mineral Poor, but great primary inputs Net importer of most primary inputs • Copper • Zinc • Aluminum • Oil Problems for Japan • Supply Disruption • Currency Swings Remedies • Yen pricing of primary products • Long term contracts • Ownership of primary commodity producers Current Approach No Text Available